What are the best breaststrokers doing now? - Persyn, U.; Colman, V. (coachesinfo.com, 1999)
The purpose of this study was to analyse the styles of the best breaststrokers, taking into account their body characteristics, to allow a kinesiological diagnosis. The styles of 65 breaststrokers at international level were digitised and the body characteristics of 574 swimmers of at least national level were tested. The styles were grouped into five variants. Because undulation, consisting of upper trunk rotations above the water and body waving, was chosen as criterion for style, concepts from animal locomotion were derived. As criterion for efficiency, the velocity variation of the body centre of mass (CMbody) was chosen. In the most undulating variant, extreme CMbody velocity variations are avoided thanks to a velocity variation of the counteracting body segments above the water, and a high and even velocity is obtained during body waving, thanks to accelerating water backward. For the education of experts in diagnosing swimmers of various performance levels, multimedia are a necessity because written outputs are not sufficiently visual.